Pengaruh Aplikasi Tiktok Terhadap Perilaku dan Karakter Siswa Sekolah Dasar (SD) - Atikah Amanda Putri; Alya Dewi Aprilianti; Isni Putri Anggraini Nurzahra; Dede Wahyudin; Jennyta caturiasari (Universitas Islam Lamongan, 2023)
This study aims to analyze the use of the Tiktok application on the behavior and character of elementary school students. The method used in this research is literature study, namely reviewing regulations, books, and journals. Based on data from several books and journals, the results obtained are that the use of the tiktok application causes two impacts, namely positive and negative impacts. For the positive there is no change in student behavior and character, while the negative impacts are changes in student behavior and character, they behave impolitely towards teachers and even parents, get emotional easily, and are indifferent to the surrounding environment because they are too engrossed in playing tiktok..